Información, conocimientos, actitudes y prácticas sobre los impactos a la salud relacionados con la contaminación ambiental por minería en el cantón Paquisha - Iñahuazo Iñahuazo, Jimena Fernanda (2015)
The balance between the environment and population, is a basic element to maintain health. However this does not happen, so that environmental pollution is a serious problem of public health at the global level, the present study identified levels and mechanisms of information, knowledge, attitudes and practices on the health impacts, related to the environmental pollution by mining, The study was qualitative quantitative cross-type; participated 176 parents of children of school age; to whom it was divided in two levels according to the closeness of the mining area in medium and high exposure. Prior informed consent of the survey, in-depth interviews and focus group, calling parents, representatives and presidents of the Parochial Boards, whose results are presented in graphs and tables. A large part of the population is engaged in mining as the main occupation, of whom 79% said they had not received information on the damage that can generate mining pollution, however the 88% indicate that there is a need to provide such information. In regard to practices, minimum percentages in both areas of exposure, they point out that the school children participating in mining activities, in some cases, the parents of family performed the extraction of gold in their homes, bring clothing and working materials to their homes, the washing of the same the carried out in conjunction with the clothes for all the family; do not make use of personal protective equipment, In terms of knowledge the parents know the harmful effects that it is the environmental pollution however continue to make these activities by being their sole source of work and how preventive attitude keep their children informed and away from the degree of pollution to which they are exposed. Key words: information, knowledge, attitudes, practices, impact, mining pollution.